Employment policy in a small-island economy : country employment review : Barbados (ILO Caribbean Office Port of SpainTT, 1999)
Provides an impressive amount of data, an overview of the principal features of Barbados' economy, including its vibrant industrial relations system, and an analysis of the specific strategies and institutions that the country has developed over time to deal with the employment problems while transiting from a closed and agriculturally-based to an open and diversified economy.
Keywords: EMPLOYMENT POLICY